Effect of Family Positive Behavior Support Nursing on CD3+, CD4+, CD4+/CD8+ and Quality of Life of Children with Malignant Tumor: CD3+, CD4+, CD4+/CD8+ and QL of malignant tumor children - Zeng, Yanfang; Tang, Juan (Cellular and Molecular Biology, 2023)
This study was to observe the effect of family-positive behavior support (PBS) nursing on the level of CD3+, CD4+, CD4+/CD8+ and quality of life (QL) of children with malignant tumor (MT). For this purpose, 96 children with MT who visited the First People’s Hospital of Chenzhou City from February 2021 to November 2022 were selected. The hospital carried out family PBS nursing in January 2022. According to the differences in the nursing methods of children, they were divided into a control group (Group C) and an observation group (Group O) with 48 cases each. Group C took routine nursing. The observation group carried out family PBS nursing based on Group C. The CD3+, CD4+, and CD4+/CD8+ levels and QL scores were compared. Results showed that after the intervention, the levels of CD3+, CD4+, CD4+/CD8+, pain and injury, nausea, anxiety during operation, treatment anxiety, anxiety, self-perception of appearance, communication problems and total scores of both groups of children were better than those before the intervention (P<0.05). After the intervention, the levels of CD3+, CD4+, CD4+/CD8+, anxiety, anxiety, cognitive problems and total scores in the observation group were significantly higher than those in Group C (P<0.05). It was concluded that family PBS nursing applied to children with MT can improve the level of CD3+, CD4+, and CD4+/CD8+. The immune system function of children was improved. It improved the anxiety, anxiety and cognitive problems of children in the operation process. At the same time, this practice can help children increase their appetite and weight, and thus promote their quality of life of children.